Regulation of Lignin Biosynthesis by Post-translational Protein Modifications - Sulis, Daniel B.; Wang, Jack P. (Frontiers in Plant Science, 2020)
Post-translational modification of proteins exerts essential roles in many biological processes in plants. The function of these chemical modifications has been extensively characterized in many physiological processes, but how these modifications regulate lignin biosynthesis for wood formation remained largely unknown. Over the past decade, post-translational modification of several proteins has been associated with lignification. Phosphorylation, ubiquitination, glycosylation, and S-nitrosylation of transcription factors, monolignol enzymes, and peroxidases were shown to have primordial roles in the regulation of lignin biosynthesis. The main discoveries of post-translational modifications in lignin biosynthesis are discussed in this review